On the Blueprint of the Long Primary Afferent Axons and the Dichotomous Axon Trajectory of Clarke's Nucleus. A Morphological Tracing Study on the Effect of Hypoxia during Development - Frits C. de Beer; Harry W. Steinbusch (MDPI AG, 2023)
The primary afferent system in the rat's spinal cord starts to develop in the third last week of gestation. First, the pseudounipolar DRG neurons extend their centripetal long primary axons, targeting rostral supra-segmental nuclei in the spinal cord. Meanwhile, the subsequent innervation of the juxta- and intra-segmental spinal levels enables the three subdivisions to commence integrating a complex network with the body periphery. This process may continue to refine and adapt the system life-long. The experimental data elucidated the steps involved in developing the cytoarchitecture by separating the axons of the long and intermediate subdivisions from the short subdivision. Here, we present a blueprint of the features of the long primary afferent axons developing in sequential waves. The pioneering long afferent axons targeted the dorsal gracile nuclei at spring tide and Clarke's nuclei at neap tide in ventrally bent trajectories. The paradigm's myelotomy blocked these pioneering fibers from stepping down the developmental cascade, rendering an unknown phenotype. This reflected a hypothetical transition hub stationed on the assembly line, delineating a critical period. The paradigm also affected the neuropil's ripening independently from the long primary afferent system. The data disclosed that fetal hyposaturation yielded an in vivo genomic engineering capability. Fetal tissue was susceptible to hyposaturation, showing remarkable versatility early in fetal life. The translational impact may favor research into the elusive etiology of clinical syndromes concerning the afferent system relating to fetal hyposaturation.